Smart Phone Enterprise / Jamri Undang ... [et al.] - Undang, Jamri; Amin, Jamal; Yudin, Mohd Rahmat; Amir, Sartina; Muhd Taib, Annahara (2009)
This business plan was prepared according to several purposes, which help the entrepreneur to realize our dream to establish the business organization which developed and competitive. One of the Business Plan's purposes is as a guideline to the entrepreneur in managing the business that they want to do and to understand more about the proposed business in order to determine the potential of the business in the future prospective. The contents of Business Plan are strongly covered many aspects so that we can run up our business and business' strategies appropriately. On the other hands, we can always remember and struggle to achieve our business' mission and vision. In addition, Business Plan help us to analyze and evaluate our business performance either advance forward or does not reach the standard level. Then, we also look for brilliant ideas on how to develop and enhance our business. We use this Business plan as a guideline to predict the sale, cash flow and financial statement. To conclude, this Business Plan enables us to be successful entrepreneurs to access our business throughly, critically and practically.